Effects of Personal Characteristics Toward Work Stress - Muhamad Zainudin (Universitas Trisakti, 2005)
This research background is constituted by the existence of requirement of bank employees to compete and improve ability. Matter like these cerlainly will be able to generate abundant job stress. The objective of this research is to prove scientifically the influence of personal characteristics like behavior, personality, and locus of control conduct of stress work as a bank employee, specially in certain part of an organization chart. The design of this research uses a field studies which are experimental and test hypothesis. Intake of sample uses a technique of non pertained probability sampling. Data analysis uses a method of enter constructive SPSS PC. Used analysis of multiple regression, seen influence three personal characteristic variables that are behavior, personality, and locus of control conduct to stress work at audit unit and also treasury unit, see influence of independent variable to job stress, job pressure, and lack of support. And also by using t -test to see the difference of the job stress, job pressure and lack of support of at both groups. Result of variable with variable ties and there are differences of stress work and lack of supports to both groups, while to job pressure there is no difference.